Hesitações em início de enunciados de crianças em aquisição de linguagem - Villega, Cristyane de Camargo Sampaio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objective: (1) to verify the existence (or not) of hesitating marks in the beginning of utterances in children‟s discourse, (2) to characterize the hesitating marks found, and (3) to determine to what extent the presence / absence of hesitation marks in the beginning of the utterances could be explained by recoverable facts in children‟s discurses. METHODS: interview situations were analyzed with four children between 5-6 years old attending Child Level II in a public school of Childhood Education at the time of data collection. The interviews were recorded on audio and video, inside a soundproof cabin, with high fidelity equipment. Afterwards, the recordings were transcribed for six transcribers specially trained for this task. Transcription rules that prioritized detection points and hesitation marks were used. For the analysis of recoverable facts in the production conditions of children‟s speech, we adopted the dialog question-answer pair. RESULTS: We observed: higher incidence of utterances initiated without hesitating marks; no statistical difference between simple and combined hesitation marks; preference for silence (silent pause and rough cut) as hesitating mark used by children in early of its utterances, followed by sound (filled pauses and hesitated stretching) and support in grammatical structures (hesitated repetition and stuttering)); correlation between the presence / absence of hesitation in the beginning of utterance and question type (open/closed) carried out by the caller since, when the question was closed type, the utterances were initiated, preferably without hesitating marks, and when the question was open type, preferably with hesitated marks. CONCLUSION: Although children have started their utterances, preferably without hesitating marks, the presence/absence of these marks and the type of the hesitating marks showed to be dependent on the condition of children‟s discourse.

Objetivos: (1) verificar a existência (ou não) de marcas hesitativas no início de enunciados no discurso de crianças; (2) caracterizar as marcas hesitativas encontradas; e (3) verificar em que medida a presença/ausência de marcas de hesitação no início desses enunciados se explicaria por fatos recuperáveis na produção dos discursos das crianças.MÉTODOS: Foram analisadas situações de entrevistas de quatro crianças com 5-6 anos de idade que frequentavam o nível Infantil II de uma escola pública de Educação Infantil na época da coleta dos dados. As entrevistas foram gravadas, em áudio e em vídeo, no interior de uma cabine acústica, com material de alta fidelidade. Posteriormente, as gravações foram transcritas por seis transcritores especialmente treinados para essa tarefa. Foram utilizadas normas de transcrição que priorizavam a detecção de pontos e de marcas de hesitações. Para a análise de fatos recuperáveis das condições de produção dos discursos das crianças, foi adotado o par dialógico pergunta-resposta. RESULTADOS: Foram observados: maior ocorrência de enunciados iniciados sem marcas hesitativas do que com essas marcas; ausência de diferença estatística entre marcas simples e marcas combinadas de hesitação; preferência pelo silêncio (pausa silenciosa e corte brusco) como marca hesitativa usada pelas crianças em inicio de seus enunciados, seguido de sonorização (pausa preenchida e alongamento hesitativo) e de apoio em estruturas gramaticais (repetição hesitativa e gaguejamento); correlação entre presença/ausência de hesitação em início de enunciado e tipo de pergunta (aberta/fechada) realizada pelo interlocutor, uma vez que, quando a pergunta era do tipo fechada, os enunciados iniciaram-se, na maioria dos casos, sem marca hesitativa e, quando a pergunta era do tipo aberta, na maioria dos casos, com marcas hesitativas. CONCLUSÃO: Embora as crianças tenham iniciado seus enunciados, na...
Keywords: Aquisição de linguagem; Educação de crianças; Crianças - Linguagem; Hesitação; Language acquisition